Transaction cost analysis of public infrastructure delivery. Issue 3 (1st June 2015) - De Schepper, Steven; Haezendonck, Elvira; Dooms, Michaël
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to offer a systematic assessment of the magnitude of transaction costs of public infrastructure delivery, based on the three attributes of transaction costs, being the asset specificity, uncertainty and frequency of a transaction. Design/methodology/approach – Non-parametric tests were used to test the transaction cost differences between different procurement types. Findings – The authors find empirical support, based on a sample of 172 public infrastructure projects in Belgium, that construction firms make higher relation specific investments to their transaction partners under a public-private partnership (PPP) than a under a traditional public procurement (TPP). In addition, the authors found that PPP transactions are burdened by a greater uncertainty and a less mature market than TPP transactions. Research limitations/implications – Given the complexity of this research, the scope is limited to: a strict distinction between two procurement types, one geographical area, a limited time scope and a focus on the private sector. Hence, the authors suggest that further research broadens the scope of either one of these aspects in order to get a better understanding of the total transaction cost burden of the public infrastructure market. Practical implications – This study offers policy makers form a better understanding of the transaction cost implications when evaluating different procurement types. Originality/value – This paper serves as one of the first systematic comparative analyses of the magnitude and determinants of transaction costs for the delivery of public infrastructure.